Supersonic shear wave elastography of in vivo pig kidney: influence of blood pressure, urinary pressure and tissue anisotropy - Gennisson, Jean-Luc; Grenier, Nicolas; Combe, Christian; Tanter, Mickaël (Ultrasound in medicine & biology, 2012)
The in vivo influence of renal anisotropy and of urinary and vascular pressure on elasticity values using ultrasonic supersonic shear wave elastography was studied in pigs. Experiments were conducted in agreement with the European Commission guidelines and directives of the French Research Ministry. Six kidneys in three pigs were studied in vivo. Elasticity of renal cortex and medulla was quantified through the shear modulus (μ) by using the supersonic shear imaging technique with an 8 MHz linear ultrasound probe. All measurements were done peroperatively both in the axis and perpendicular to the main axis of pyramids, in normal condition, after progressive increase of urinary pressure, and after renal artery and renal vein ligation. In normal conditions, cortical (C) and medullary (M) elasticity values were always higher when acquisitions were realized with the ultrasound main axis perpendicular to main pyramid axis (C(//): 7.7 ± 2.3 kPa; M(//): 8.7 ± 2.5 kPa) than parallel (C(⊥): 6.9 ± 1.4 kPa; M(⊥): 6.6 ± 2.3 kPa), demonstrating an effect of renal anisotropy. In renal cortex, two bands were separated, inner cortex showing higher elasticity values (IC(⊥): 8.1 ± 1.9 kPa) than outer cortex (OC(⊥): 6.9 ± 1.4 kPa). Renal artery and renal vein ligation induced a decrease and an increase of elasticity respectively. Parenchymal elasticity increased linearly with elevation of urinary pressure. Intrarenal elasticity values vary with tissue anisotropy and, with vascular and urinary pressure levels. These parameters have to be taken into account for interpretation of tissue changes. Separation of outer and inner cortex could be attributable to perfusion differences.